Role of psychosocial factors and serotonin transporter genotype in male adolescent criminal activity. (3rd June 2014) - Qiu, Changjian; Zhao, Liansheng; Liu, Xiang; Yu, Yue; Meng, Yajing; Wu, Jia; Luo, Yupeng; Lai, Lin; Wen, Feng; Lin, Dongtao; Wang, Xiaoping; Zhang, Wei; et al.
Abstract Introduction Violent behavior is influenced by various environmental factors and the serotonergic circuitry alike. Nevertheless, studies on relations among genes, personality, social environment, and juvenile violent behavior are limited, and there is no such study in China. Methods In the current study, we aimed to investigate the contribution of serotonin transporter (5‐HTT) polymorphisms to the development of violence and to explore the relations among genes, personality, social environment, and juvenile violent behavior in China. We recruited 213 male adolescents with violent crime history and 145 male adolescents without violent crime history. The association between each risk factor and violent behavior for all the participants was examined, and the interrelation of the domains (personality, family, social support, coping style, impulsivity, and aggression) and the adolescents' violent behavior was analyzed. Chi‐square test was used to examine the association between genotypes and violent behavior. Results Adolescents with a violent crime history had lower education levels, higher neuroticism and psychoticism, but lower dissimulate. Social support and coping style were significantly associated with their criminal behaviors. Discussion The 5‐HTTLPR genotype distributions differed significantly between the violent and nonviolent groups.